Six Immune Associated Genes Construct Prognostic Model Evaluate Low-Grade Glioma - Tan, Yin Qiu; Li, Yun Tao; Yan, Teng Feng; Xu, Yang; Liu, Bao Hui; Yang, Ji An; Yang, Xue; Chen, Qian Xue; Zhang, Hong Bo (Frontiers in Immunology, 2020)
Background: The immunotherapy of Glioma has always been a research hotspot. Although tumor associated microglia/macrophages (TAMs) proves to be important in glioma progression and drug resistance, our knowledge about how TAMs influence glioma remains unclear. The relationship between glioma and TAMs still needs further study. Methods: We collected the data of TAMs in glioma from NCBI Gene Expression Omnibus (GEO) that included 20 glioma samples and 15 control samples from 4 datasets. Six genes were screened from the Differential Expression Gene through Gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, protein protein interaction (PPI) network and single-cell sequencing analysis. A risk score was then constructed based on the six genes and patients’ overall survival rates of 669 patients from The Cancer Genome Atlas (TCGA). The efficacy of the risk score in prognosis and prediction was verified in Chinese Glioma Genome Atlas (CGGA). Results: Six genes, including CD163, FPR3, LPAR5, P2ry12, PLAUR, SIGLEC1, that participate in signal transduction and plasma membrane were selected. Half of them, like CD163, FPR3, SIGLEC1, were mainly expression in M2 macrophages. FPR3 and SIGLEC1 were high expression genes in glioma associated with grades and IDH status. The overall survival rates of the high risk score group was significantly lower than that of the low risk score group. Conclusion: Joint usage of the 6 candidate genes may be an effective method to diagnose and evaluate the prognosis of glioma, both in Low-grade glioma (LGG) and High-grade glioma (HGG). Keywords: Glioma, Tumor associated macrophage, Single cell sequence, Prognosis, Biomarker